Synthesis of fused B, N-heterocycles by alkyne cleavage, NHC ring-expansion and C–H activation at a diboryne. Issue 47 (20th May 2019) - Brückner, Tobias; Arrowsmith, Merle; Heß, Merlin; Hammond, Kai; Müller, Marcel; Braunschweig, Holger
Abstract : The addition of alkynes to a saturated N-heterocyclic carbene (NHC)-supported diboryne results in spontaneous cycloaddition, with complete BB and CC triple bond cleavage, NHC ring-expansion and activation of a variety of C–H bonds, leading to the formation of complex mixtures of fused B, N-heterocycles. Abstract : The addition of alkynes to a saturated N-heterocyclic carbene (NHC)-supported diboryne results in spontaneous cycloaddition, with complete BB and CC triple bond cleavage, NHC ring-expansion and activation of a variety of C–H bonds, leading to the formation of complex mixtures of fused B, N-heterocycles.